Effect of Dietary β-hydroxy-β-methylbutyrate Calcium on Carcass Cuts, Serum Biochemistry, Bone Characteristics and Digestive Tract pH of Broiler Chickens - Ahmed , Suad Kh.; Rasheed, Eman Allaa (International Journal of Poultry Science, 2017)
Objective: This study aimed to investigate the effect of dietary β-hydroxy-β-methylbutyrate calcium (HMB-Ca) on the main carcass cuts, serum biochemistry, bone characteristics and digestive tract pH of broiler chickens. Materials and Methods: A total of 216 day-old chicks of strain Ross-308 were distributed into 4 groups dietary fed HMB-Ca at different concentrations (0.0, 0.1, 0.15 and 0.2%). The HMB-Ca was administered from 1-35 days of age. Duncan’s multiple range test was used to compare means. Results: The results showed that 0.2% HMB-Ca increased (p<0.05) breast and thighs percentage, serum alkaline phosphatase (ALP), high-density lipoprotein (HDL) and femur and metatarsus phosphorus (P) but decreased serum cholesterol. Dietary HMB-Ca decreased (p<0.01) triglycerides (TG), very-low-density lipoprotein (VLDL) (p<0.05) and the pH of the crop and gizzard contents. The administration of 0.1 and 0.2% HMB-Ca increased (p<0.05) serum calcium (Ca). Dietary HMB-Ca had no effect on the length or weight of the femur and metatarsus bones. Conclusion: It is concluded that adding HMB-Ca, especially at the level of 0.2%, to the diet of broiler chickens may increase the development of breast and thigh muscles and decrease the levels of harmful serum lipids, in addition to its effect on the metatarsus bone mineral content and the pH of the contents of the digestive tract.